Artificial coral-derived ceramic material: A technological development for a sustainable carbon capture system (2021)
Coral reefs are undergoing major transitions that threaten their natural functioning and resilience. These changes may modify reef ecology and geomorphology in various ways, especially in the form of reduced topographic complexity and carbon capture capacity. In the same way, offsetting carbonate production consists of processes that erode reef framework either through dissolution or through conversion to sediment. Geologically speaking, carbonate is also added through physicochemical and biologically mediated lithification (i.e., generation of coral rubble). The invention patent (Patent No. NC2022/0000142, Patent pending) presented here, owned by the University of the Andes, allows the production of artificial porous coral probes (ceramic material) with controlled density and porosity. This study presents the manufacturing process of the ceramic material and a sintering method from a controlled mixture of coral debris aggregates, organic algal-based binders, and generators of porosity. Once the sintering and water removal process has taken place is worth heeding that one of the most important aspects of the artificial coral is the generation of a complex connected porous system that allows rapid-flux marine colonization and may facilitate biological functions enhancing carbon storage capacity. Because the mold tooling on which the sintering takes place can be of any shape and size, so can the sintered coral-derived ceramic probes and its mechanical characteristics be of a range described for stony corals including chemical-physical characteristics discussed here such as bulk, solid, and skeletal density, connected and isolated porosity, pore-size distribution, physical and chemical heterogeneity.